2020
DOI: 10.3389/fphys.2020.538701
|View full text |Cite
|
Sign up to set email alerts
|

Biliary-Atresia-Associated Mannosidase-1-Alpha-2 Gene Regulates Biliary and Ciliary Morphogenesis and Laterality

Abstract: Background/Aims: Infectious and genetic factors are invoked, respectively in isolated biliary atresia (BA), or syndromic BA, with major extrahepatic anomalies. However, isolated BA is also associated with minor extrahepatic gut and cardiovascular anomalies and multiple susceptibility genes, suggesting common origins.Methods: We investigated novel susceptibility genes with genome-wide association, targeted sequencing and tissue staining in BA requiring liver transplantation, independent of BA subtype. Candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 32 publications
(48 reference statements)
2
24
0
Order By: Relevance
“…We have previously shown downregulation of the ciliary genes, Ift74, and Dnah11 in the liver, and of the protein Arl13b in the lungs of untreated Man1a2 −/− mutants (So et al, 2020). Here we found that NAC exposure resulted in upregulation of all three genes in lung tissue from newborn pups of all genotypes (Supplementary Table 2).…”
Section: Gestational Nac Treatment Improves Lung Ciliation and Ciliary Genesupporting
confidence: 63%
See 4 more Smart Citations
“…We have previously shown downregulation of the ciliary genes, Ift74, and Dnah11 in the liver, and of the protein Arl13b in the lungs of untreated Man1a2 −/− mutants (So et al, 2020). Here we found that NAC exposure resulted in upregulation of all three genes in lung tissue from newborn pups of all genotypes (Supplementary Table 2).…”
Section: Gestational Nac Treatment Improves Lung Ciliation and Ciliary Genesupporting
confidence: 63%
“…The benefit of NAC treatment on survival likely resulted from augmented ciliogenesis as suggested by upregulation of the ciliary genes, Arl13b, Dnah11, and Ift74 in lungs of NAC-treated newborn pups with each genotype (Supplementary Table 3). We have previously reported reduced expression of these genes or corresponding proteins in Man1a2 null compared with WT newborn pups (So et al, 2020). Interestingly NAC treatment also enhanced Man1a2 exon 2 transcription in lungs from heterozygous and WT pups but not in null pups who lacked the exon 2 DNA sequence.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations